Investigation of Groundwater Potential in Marsela and Bululora Villages, Masela Island, Southwest Maluku District Using VES and LEM Resistivity Data - Matheus Souisa; Sisca M Sapulete; Sean O O. Souisa; Cici C.N. Ohoiner; Raras F Waimalaka; Leona Y Mataheruilla; Sansina L Pangely (Department of Physics, Sebelas Maret University, 2025)
Groundwater has a wider distribution than surface water because groundwater fills all the pores of the rocks and soil beneath the earth's surface. Groundwater is located in a layer of soil called the aquifer layer which can be identified by the resistivity geoelectric method. The hydrogeological survey conducted in this study included the characterization of aquifers such as rock types and aquifer types through the interpretation of subsurface conditions using the geoelectric resistivity mapping (LEM) method with the Wenner-Schlumberger configuration and sounding (VES) with the Schlumberger configuration. The results showed that the MarselaVes-1 (GeoM-01), MarselaVes-2 (GeoM-02), and BululoraVes-1 (GeoB-01) point areas have local aquifers with moderate productivity and wide distribution. These three geoelectric points have the potential for drilling. Meanwhile, the hydrogeology at the BululoraVes-2 (GeoB-2) point has an aquifer with low productivity.